Efficiency and Health Economic Evaluations of BD OneFlow™ Flow Cytometry Reagents for Diagnosing Chronic Lymphoid Leukemia. Issue 6 (2nd April 2019) - Moloney, Eoin; Watson, Helen; Barge, Dawn; Allen, A. Joy; Carey, Peter; Hislop, Jennifer; Johnston, Louise; Lorrison, Kate; McGregor, Andrew; O'Leary, Rachel A.; Power, Michael H.; Wallis, Jonathan; et al.
Abstract : Reason for the study: To standardize the use of flow cytometry for classifying hematological malignancies and make the results reliable and reproducible across laboratories, the EuroFlow™ Consortium published a comprehensive specification of antibody‐fluorochrome conjugates, standard protocols, and algorithms for analysis. The BD OneFlow™ system builds on, and further standardizes, the EuroFlow protocols. We aimed to assess the effects on safety, efficiency, and costs for laboratories of adopting the BD OneFlow reagent tubes (LST and B‐CLPD T1) for diagnosing chronic lymphocytic leukemia. Methods: We compared in‐house laboratory processes and results with those using the LST and B‐CLPD T1 reagent tubes with, and without, blood film morphology. Outcome measures included concordance in classification results, and efficiency within the laboratory, that is, resource usage, staff time, unwanted events, and cost‐consequences. Results: There was 100% concordance between the classifications made with in‐house flow cytometry and those with the BD OneFlow reagent tubes. Using BD OneFlow tubes required 13 hours less staff time per month (i.e. for 100 samples) than the in‐house process. Sensitivity analyses explored the effects of uncertainties in the price of the BD OneFlow tubes and the prevalence of CLL and identified the thresholds at which laboratories might expect cost‐savings from adopting the BD OneFlow system. Laboratory and clinical staff considered the BD OneFlow system to be safe and effective. Conclusions: Laboratories adopting the BD OneFlow system for classifying patients with suspected CLL can expect safe, efficient processes that can be cost saving if the discount on the list price, and prevalence of CLL (which will both vary between sites and countries), is within the thresholds suggested by the health economics sensitivity analysis. © 2019 International Clinical Cytometry Society